Reduction in primary genu recurvatum gait after aponeurotic calf muscle lengthening during multilevel surgery - Klotz, Matthias C. M.; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Krautwurst, Britta; Braatz, Frank; Dreher, Thomas (Research in developmental disabilities, 2013)
Knee hyperextension (genu recurvatum, GR) is often seen in children with bilateral spastic cerebral palsy (CP). Primary GR appears essential without previous treatment. As equinus deformity is suspected to be one of the main factors evoking primary GR, the purpose of this study was to determine whether lengthening the calf muscles to decrease equinus would decrease coexisting GR in children with bilateral spastic CP. In a retrospective study, 19 CP patients with primary GR (mean age: 9.4 years, 13 male, 6 female, 26 involved limbs) in whom an aponeurotic calf muscle lengthening procedure was performed during single-event multilevel surgery were included and investigated using three-dimensional gait analysis before and at a mean follow-up of 14 months after the procedure according to a standardized protocol. After calf muscle lengthening, a significant improvement in ankle dorsiflexion (9.5°) and a significant reduction (10.5°) in knee hyperextension (p<0.001) were found during mid-stance of the gait cycle. Six limbs (23%) showed no improvement concerning knee hyperextension and were designated as nonresponders. In these patients no significant improvement in ankle dorsiflexion was found after surgery either. Improvement in ankle dorsiflexion and reduction in knee hyperextension in stance phase correlated significantly (r=0.46; p=0.019). These findings indicate that equinus deformity is a Major underlying factor in Primary GR and that calf muscle lengthening can effectively reduce GR in patients with CP.
Gesehen am 08.06.2022